3(13-2a)=-13+a

Simple and best practice solution for 3(13-2a)=-13+a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(13-2a)=-13+a equation:


Simplifying
3(13 + -2a) = -13 + a
(13 * 3 + -2a * 3) = -13 + a
(39 + -6a) = -13 + a

Solving
39 + -6a = -13 + a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1a' to each side of the equation.
39 + -6a + -1a = -13 + a + -1a

Combine like terms: -6a + -1a = -7a
39 + -7a = -13 + a + -1a

Combine like terms: a + -1a = 0
39 + -7a = -13 + 0
39 + -7a = -13

Add '-39' to each side of the equation.
39 + -39 + -7a = -13 + -39

Combine like terms: 39 + -39 = 0
0 + -7a = -13 + -39
-7a = -13 + -39

Combine like terms: -13 + -39 = -52
-7a = -52

Divide each side by '-7'.
a = 7.428571429

Simplifying
a = 7.428571429

See similar equations:

| x-5=-2x+13 | | X+80+2x+20=180 | | X/4-x/12=1/2 | | 10r+15=33-12r-52 | | 5-2x/-3-4-x | | [u-7]=-1/4 | | y-9=4/6(x-3) | | -9y-18=9(y-6) | | 2(a+4)=-3(7x+2)+8x | | -2(x-4)=(3-x) | | 3[-2(x+5)-5]=x+7 | | (y^4)-12*(y^3)+48*(y^2)-145*y+90=0 | | P^4-11p^2+1=0 | | y^4-12y^3+48y^2-145y+90=0 | | 11-15=6x-5-5x | | 3x-6+10=14 | | [-2x]=[8] | | 12=14x-11x | | -3(5-9v)=25+7w | | -8x+5y=131 | | x+47=-72 | | 3x-y=76 | | 3(3+6x)=-81 | | 6(m-21)=12 | | -4x-6=-4x-4 | | 5x+25=-30 | | 3x/4=21/1 | | 16x-10y=124 | | 8(x-2)=(x+2) | | x^2+y^2=130 | | 2b/5=10 | | 7x-5+12x+10= |

Equations solver categories